Mechanism of the Immunomodulatory Effect of the Combination of Live Bifidobacterium, Lactobacillus, Enterococcus, and Bacillus on Immunocompromised Rats - Lv, Longxian; Mu, Deguang; Du, Yiling; Yan, Ren; Jiang, Huiyong (Frontiers in Immunology, 2021)
Immunodeficiency is a very common condition in suboptimal health status and during the development or treatment of many diseases. Recently, probiotics have become an important means for immune regulation. The present study aimed to investigate the mechanism of the immunomodulatory effect of a combination of live Bifidobacterium, Lactobacillus, Enterococcus, and Bacillus (CBLEB), which is a drug used by approximately 10 million patients every year, on cyclophosphamide-immunosuppressed rats. Cyclophosphamide (40 mg/kg) was intraperitoneally injected to induce immunosuppression in a rat model on days 1, 2, 3, and 10. Starting from day 4, the rats were continuously gavaged with CBLEB solution for 15 days. The samples were collected to determine routine blood test parameters, liver and kidney functions, serum cytokine levels, gut microbiota, fecal and serum metabolomes, transcriptomes, and histopathological features. The results indicated that CBLEB treatment reduced cyclophosphamide-induced death, weight loss, and damage to the gut, liver, spleen, and lungs and eliminated a cyclophosphamide-induced increase in the mean hemoglobin content and GGT, M-CSF, and MIP-3α levels and a decrease in the red blood cell distribution width and total protein and creatinine levels in the blood. Additionally, CBLEB corrected cyclophosphamide-induced dysbiosis of the gut microbiota and eliminated all cyclophosphamide-induced alterations at the phylum level in rat feces, including the enrichment in Proteobacteria, Fusobacteriota, and Actinobacteriota and depletion of Spirochaetota and Cyanobacteria. Furthermore, CBLEB treatment alleviated cyclophosphamide-induced alterations in the whole fecal metabolome profile, including enrichment in 1-heptadecanol, succinic acid, hexadecane-1,2-diol, nonadecanoic acid, and pentadecanoic acid and depletion of benzenepropanoic acid and hexane. CBLEB treatment also alleviated cyclophosphamide-induced enrichment in serum D-lyxose and depletion of serum succinic acid, D-galactose, L-5-oxoproline, L-alanine, and malic acid. The results of transcriptome analysis indicated that the mechanism of the effect of CBLEB was related to the induction of recovery of cyclophosphamide-altered carbohydrate metabolism and signal transduction. In conclusion, the present study provides an experimental basis and comprehensive analysis of application of CBLEB for the treatment of immunodeficiency.